(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
In this study we conducted a field study of the most important household, industrial and commercial plastic wastes in Lattakia Governorate and studied the most important effects of plastic waste production and use. HDPE and LDPET were selected for recycling. The best ratios were determined for mixing recycled polyethylene with pure polyetylene. In addition, the most important mechanical properties of recycled and produced plastics were examined. To productive agricultural pipes. In the study of the mechanical properties of the studied samples, the best ratios for mixing the recycled plastic with the pure were (15%) rounded, the studied mixtures had the values ​​of the flow guide between the round 0% and the round 100% and the closest to 0% was the 15% 15%) relatively low activation energy compared to other mixtures, and pressure by 9 Bar and maintained its strength, which is consistent with the Syrian standards.